A Review of Carbon Market Policies and Research - Larson, Donald F. (2012)
We describe important institutions that shape climate change policies together with a set of key market-reliant instruments. We selectively review the related economic literature, emphasizing empirical studies that assess the efficacy of current policies and the workings of policy-dependent markets. Special attention is given to new carbon finance markets tied to the Kyoto Protocol's flexibility mechanisms. Promising areas for future research are identified.